2021
DOI: 10.1007/s12649-021-01507-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of Organic Briquettes from Slaughterhouse Waste as Nutrient Source for Plant Growth

Abstract: A study was conducted to develop organic briquettes using biomass originating from slaughterhouse wastes and to investigate its potential as a nutrient source for plant growth.Dried rumen contents were mixed with fresh blood collected after bleeding of animals in different proportions and dried using tray drier. The dried rumen content-blood (RB) mixture was further mixed with commercially available coir pith in 12 different proportions. The rumen content-blood-coir pith (RBC) mixture was formed into briquette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Anaerobic digestion, on other hand, a multi-stage biological process, is generally carried out in mesophilic conditions (at 35 • C) for much longer durations (15-30 days) and/or thermophilic conditions (at 55 • C) for 12-14 days [43]. The high proteinaceous matter of blood makes it a problematic substrate for anaerobic digestion [23]. Moreover, implementation of anaerobic digestion in India has recurrently failed in the real field situation due to impractical suppositions on biowaste quality and quantity, miscalculation of the complicated biowaste supply chain, inappropriate anaerobic digestion designs and misjudgment of financial returns from biogas and digestate [44].…”
Section: Waste Recycling Through the Drying Processmentioning
confidence: 99%
See 4 more Smart Citations
“…Anaerobic digestion, on other hand, a multi-stage biological process, is generally carried out in mesophilic conditions (at 35 • C) for much longer durations (15-30 days) and/or thermophilic conditions (at 55 • C) for 12-14 days [43]. The high proteinaceous matter of blood makes it a problematic substrate for anaerobic digestion [23]. Moreover, implementation of anaerobic digestion in India has recurrently failed in the real field situation due to impractical suppositions on biowaste quality and quantity, miscalculation of the complicated biowaste supply chain, inappropriate anaerobic digestion designs and misjudgment of financial returns from biogas and digestate [44].…”
Section: Waste Recycling Through the Drying Processmentioning
confidence: 99%
“…Existing industrial scale drying units such as flash drum dryers, spray dryers, bio drying and fried drying have complicated mechanisms and expensive attachments. The present methods for the disposal of rumen digesta are ensiling and drying by fluidized bed dryer, which entails high processing and operational costs [23]. Therefore, rural slaughterhouses, lacking in facilities, resources and infrastructure, Whereas García-Bernet et al [48] represented a schematic of a drying curve that showed a plot between evaporation flux and mean moisture content for anaerobic digestion, no characteristic curves were reported.…”
Section: Experimental Drying Curves Obtained During the Drying Processmentioning
confidence: 99%
See 3 more Smart Citations